Regulatory nucleotides involved in the Rel function of Bacillus subtilis. - Nishino, T (1979)
We have examined the accumulation of polyphosphorylated nucleotides in Bacillus subtilis in relation to the function of the rel gene. Our results are as follows. (i) During inhibition of isoleucine activation by O-methylthreonine, wildtype B. subtilis cells accumulate unusual nucleotides with the chromatographic and chemical properties of pppApp, ppApp, pppGpp, ppGpp, pGpp, and ppGp. (ii) During the carbon source downshift elicited by inhibiting glucose uptake, we observed accumulation of the polyphosphorylated guanosine but not adenosine nucleotides. (iii) At the end of long phase in sporulation medium, we observed a small transient accumulation of the polyphosphorylated guanosine but not adenosine nucleotides. (iv) We were unable to detect a nucleotide with chromatographic behavior expected for pppAppp under any conditions. (v) The rel mutant of Swanton and Edlin (Biochem. Biophys. Res. Commun. 46-583-588, 1972) did not accumulate any of these polyphosphorylated nucleotides under any of the conditions examined. (vi) the rel mutant is unimpaired in sporulation. We conclude that one or more of the nucleotides we have detected may be involved in controlling the specificity of transcription during the stringent response, but none of them are required for sporogenesis.